2017
DOI: 10.1177/1071100717735289
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Hallux Rigidus Grade With Motion, VAS Pain, Intraoperative Cartilage Loss, and Treatment Success for First MTP Joint Arthrodesis and Synthetic Cartilage Implant

Abstract: Level II, randomized clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 12 publications
1
30
0
2
Order By: Relevance
“…In addition to patient-reported outcomes, other studies have also evaluated range of motion or radiographic outcomes, which were not evaluated in our study. 2 , 4 Our cohort was also not subdivided by grade of hallux rigidus, though indication for operative intervention with PVA implant at our institution typically includes patients with grade II or grade III hallux rigidus based on the Coughlin scale. 5 A prior study assessing hemiarthroplasty with PVA hydrogel implant based on hallux rigidus grade showed that the implant can be used successfully for patients with grade II, III, or IV hallux rigidus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to patient-reported outcomes, other studies have also evaluated range of motion or radiographic outcomes, which were not evaluated in our study. 2 , 4 Our cohort was also not subdivided by grade of hallux rigidus, though indication for operative intervention with PVA implant at our institution typically includes patients with grade II or grade III hallux rigidus based on the Coughlin scale. 5 A prior study assessing hemiarthroplasty with PVA hydrogel implant based on hallux rigidus grade showed that the implant can be used successfully for patients with grade II, III, or IV hallux rigidus.…”
Section: Discussionmentioning
confidence: 99%
“…Cheilectomy, at times with proximal phalanx osteotomy, is typically reserved for mild to moderate hallux rigidus, 2,9,16,20 whereas arthrodesis is the most predictable procedure for severe hallux rigidus. 1,2,5,11,21…”
Section: Introductionmentioning
confidence: 99%
“…8 Arthrodesis remains the gold standard for severe hallux rigidus, although promising results have been shown recently with a synthetic cartilage implant. 1 A dorsal cheilectomy can be performed for patients in early stages of hallux rigidus. This can result in good relief of their symptoms provided that it mainly consists of impingement pain and stiffness in the absence of mid-range pain and a negative grind test.…”
mentioning
confidence: 99%